2020
DOI: 10.1097/tp.0000000000003536
|View full text |Cite
|
Sign up to set email alerts
|

Solid Organ Transplantation in the Era of COVID-19: Lessons from France

Abstract: Coronavirus disease 2019 (COVID-19) outbreak has significantly upended solid organ transplant (SOT) practice around the world. Early reports confirmed the heavy burden of COVID-19 in SOT recipients with mortality rates reaching up to 35%. Because most transplant recipients harbored multiple comorbidities known to be associated with a severe course of COVID-19, the true impact of immunosuppression by itself remained an unsolved issue. Transplant societies have initially recommended to postpone nonurgent renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 63 publications
2
31
0
5
Order By: Relevance
“…We found that, of our KTRs who reported a household contact with a known Covid-19 case, 34% had anti-SARS-CoV-2 antibodies. Because a similar frequency was described in the Spanish serosurvey (37.4%), 2 we believe that active prevention and control measures to limit virus spread should be vigorously implemented for the KTR population.…”
Section: Discussionsupporting
confidence: 70%
“…We found that, of our KTRs who reported a household contact with a known Covid-19 case, 34% had anti-SARS-CoV-2 antibodies. Because a similar frequency was described in the Spanish serosurvey (37.4%), 2 we believe that active prevention and control measures to limit virus spread should be vigorously implemented for the KTR population.…”
Section: Discussionsupporting
confidence: 70%
“…1,2 Despite the urgent need for many waitlisted patients worldwide to receive transplants, preliminary data suggest substantial reductions in transplantation procedures in some countries since the COVID-19 outbreak. [3][4][5][6][7][8][9][10][11] However, there is a paucity of available data concerning the effects of the pandemic on worldwide transplantation rates and how transplantation policies have changed in response to risk of infection and death associated with COVID-19. [12][13][14] The consequences of COVID-19 are not only due to infectious deaths but also the impact of the pandemic on diverse health-care services, including disruptions to or delays in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While no specific data from trials including transplant recipients with COVID-19 have been published so far, concerns have been raised on the off-label and potentially harmful use of targeted therapies. 12,13 Several variabilities also exist in managing immunosuppression. In the United States, centers were less likely to administer T-cell depleting agents (TDA) for induction.…”
mentioning
confidence: 99%
“…14 In terms of maintenance immunosuppression, depending on the patient's symptoms, a stepwise reduction in immunosuppression is recommended. 1,12,[14][15][16] There is a dearth of literature in practices related to non-hospitalized transplant recipients with COVID-19 and prevalent transplant recipients.…”
mentioning
confidence: 99%